Transcriptomic and proteomic profiles of vascular cells involved in human abdominal aortic aneurysm - Pinet, Florence; Lamblin, Nicolas; Ratajczak, Philippe; Hot, David; Dubois, Emilie; Chwastyniak, Maggy; Beseme, Olivia; Drobecq, Hervé; Lemoine, Yves; Koussa, Mohammad; Amouyel, Philippe (IntechOpen, 2011)
None